Health risk behaviors and injured patients: an exploratory study. (1st March 2011) - Degutis, C; Busch, S; Pantalon, M; Fiellin, D; O'Connor, P; D'Onofrio, G
Abstract : Objective: To determine whether patients presenting to the emergency department (ED) with injury were more likely to report risky health behaviours than pts without injury. Methods: Adult (age>18) patients with non-life-threatening injury or illness presenting to the ED were screened for following: alcohol consumption, smoking, exercise, seatbelt and helmet use. Results: 16 299 patients were screened; 5327 (33.5%) with injuries; 6868 (43.2%) male. Injured pts were significantly more likely to be male (36.4% vs 31.4%; p=0.000), younger (43.7 vs 46.1; 95% CI 1.85 to 3.10), drink alcohol (39% vs 36%; p=0.003); exercise regularly (57.9% vs 50.7%; p=0.000); and significantly less likely to wear a seatbelt regularly (33.6% vs 66.4%; p=0.000). There was no difference in reported cigarette smoking between injured and non-injured patients (66.9% vs 67.7%, p=0.331). There were no significant differences in drinking patterns (# of days of drinking per week, usual # of drinks per occasion, maximum # of drinks per occasion) between injured and non-injured patients. Conclusions: While there were differences in some health behaviours (alcohol consumption, exercise and seatbelt use) between injured and non-injured pts presenting to the ED, there were no differences in drinking patterns between injured and non-injured patients who reported any alcohol consumption. This supports the need to continue to screen for alcohol problems and provide interventions for all ED patients.